Clinical Characteristics and Outcome of Patients With Pheochromocytoma: A Single Center Tertiary Care Experience - Sohail, Sara (Cureus, 2020)
Objective The aim of this study was to evaluate the demographic and clinical characteristics of patients with pheochromocytoma and determine the treatment outcome with overall survival rates of patients with pheochromocytoma. Methods A retrospective, cross-sectional study was performed on all the patients with histologically proven pheochromocytoma presenting to Shaukat Khanum Memorial Cancer Hospital and Research Center (SKMCH & RC) Lahore, between August 2006 and July 2018. Clinical, biochemical and radiological data were collected at presentation, post-surgery, at discharge and till the last follow-up; data was retrieved from hospital records. Cure was defined as no evidence of disease biochemically, clinically, and structurally. Results This study included 29 patients, 69% were female. The three most common symptoms were abdominal pain (51.7%), hypertension (44.8%) and headache (41.4%). Most pheochromocytomas were sporadic (82.8%), all were adrenal gland tumors, and 89.7% were unilateral. All patients underwent adrenalectomy. Open adrenalectomy was performed in 25 patients whereas four underwent laparoscopic adrenalectomy. Fifteen patients experienced postoperative complications. The most frequently documented intraoperative complication was hypotension. Death occurred in two patients, one patient died of metastatic disease secondary to malignant pheochromocytoma and the other patient died from perioperative complications. Cure was documented biochemically and/or radiologically in 96.5% patients. Conclusions Abdominal pain was predominant presenting feature most likely due to large tumor size. Most patients presenting to SKMCH & RC, had large intra-abdominal tumors with high cure rate. Mortality was low despite high rate of perioperative complications.